Cell cycle regulation of the cyclin A gene promoter is mediated by a variant E2F site. - Schulze, A (1995)
Cyclin A is involved in the control of S phase and mitosis in mammalian cells. Expression of the cyclin A gene in nontransformed cells is characterized by repression of its promoter during the G1 phase of the cell cycle and its induction at S-phase entry. We show that this mode of regulation is mediated by the transcription factor E2F, which binds to a specific site in the cyclin A promoter. It differs from the prototype E2F site in nucleotide sequence and protein binding; it is bound by E2F complexes containing cyclin E and p107 but not pRB. Ectopic expression of cyclin D1 triggers premature activation of the cyclin A promoter by E2F, and this effect is blocked by the tumor suppressor protein p16INK4.